Stanje slovenskega podjetništva in izzivi izobraževanja za podjetnost: Slovenski podjetniški observatorij 2013 - Rebernik, Miroslav; Širec, Karin; Močnik, Dijana (2014)
Condition of Slovenian Entrepreneurship and the Challenges of Entrepreneurship Education : Slovenian Entrepreneurship Observatory 2013. In this monograph, we analysed all the companies and entrepreneurs in Slovenia in 2012 and then, for 2010, we compared the critical data for companies from the EU-27 and Slovenia in the activities of industry, trade and services. In Slovenia in 2012, 132,051 companies employed almost 536,000 people. Most businesses (19%) were operating in trade, maintenance and repair of motor vehicles. Created added value amounted to 19.25 billion euro. Within the second part, we point to the importance of entrepreneurship in the modern society and its impact on the economic and social development. We show the state of entrepreneurship education in Slovenia and analyse its basic obstacles and success factors, as well as give some recommendations for overcoming them. One such recommendation is establishing an appropriate strategy for entrepreneurship education at the higher education level, although this cannot be separated from the general entrepreneurship education strategy or from the general framework for the promotion of entrepreneurship.
Keywords: podjetniška demografija; EU-27 nefinančni sektor gospodarstva; primerjalna analiza; podjetniško izobraževanje; ovire podjetniškega izobraževanja; Companies Demography; EU-27 Non-Financial Business Sector; Comparative Analysis; Entrepreneurship Education; Barriers to Entrepreneurship Education